2003
DOI: 10.1590/s0034-89102003000100011
|View full text |Cite
|
Sign up to set email alerts
|

Emprego em serviços domésticos e acidentes de trabalho não fatais

Abstract: OBJETIVO: Estimar a incidência anual de acidentes não fatais de acordo com variáveis sociodemográficas e ocupacionais entre empregadas em serviços domésticos. MÉTODOS: Inquérito de base comunitária conduzido com 1.650 mulheres de 10 a 65 anos de idade, que referiram ter atividade remunerada e que compunham uma amostra aleatória por conglomerados dos domicílios da cidade de Salvador, capital da Bahia. Os dados foram obtidos por meio de questionários individuais sobre condições de vida, trabalho e saúde. Foi uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 4 publications
(3 reference statements)
0
2
0
5
Order By: Relevance
“…They had a risk of maternal death almost four times higher than the referent group. Domestic workers are known for long working hours, commonly above eight hours a day and more than five days a week, in more than one workplace, although they have low wages 23 . A large study on the prevalence of occupational risk factors in pregnancy from Spain found more than 20% for orthostatism, lifting load above 5 kg, intense work rhythms, continuous attention, repetitive and monotonous tasks, work-related stress, lack of support from colleagues and supervisors, social isolation, excessive noise, extreme temperatures and humidity, electromagnetic fields and other physical risk agents 24 .…”
Section: Discussionmentioning
confidence: 99%
“…They had a risk of maternal death almost four times higher than the referent group. Domestic workers are known for long working hours, commonly above eight hours a day and more than five days a week, in more than one workplace, although they have low wages 23 . A large study on the prevalence of occupational risk factors in pregnancy from Spain found more than 20% for orthostatism, lifting load above 5 kg, intense work rhythms, continuous attention, repetitive and monotonous tasks, work-related stress, lack of support from colleagues and supervisors, social isolation, excessive noise, extreme temperatures and humidity, electromagnetic fields and other physical risk agents 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between gender and work has been explored throughout the study period but production has been scarce and centered in two institutions: Fiocruz, [16][17][18]78 and UFBA, through its two research groups -Programa de Estudos em Gênero e Saúde (MUSAGender and Health Studies Program) 6,9 and Programa de Investigação sobre a Saúde do Trabalhador (PISATProgram of Environmental and Worker's Health) 80,81 in the Instituto de Saúde Coletiva. On this theme, some epidemiological studies exploring the link between gender and health stand out, as does an update on breastfeeding from female workers' perspective.…”
Section: What the Scientific Production Is Aboutmentioning
confidence: 99%
“…12 Poucos estudos sobre acidentes, com grupos populacionais específicos, trazem informações sobre raça/cor de pele; os resultados encontrados no estudo atual podem ratificar outros que identificam homens de cor preta e mulheres negras mais acometidos de violência e acidentes do que outros grupos raciais. 21,24 Na Gamboa de Baixo a incidência foi apenas de acidentes leves. Um estudo em 10% dos domicílios urbanos de Dharan, no Nepal, encontrou "prevalência" de 3,5% por ano para injúrias "menores" por mês e de 0,7% para injúrias "maiores".…”
Section: Introductionunclassified